PKM PEMBERDAYAAN USAHA PRODUK PANGAN KELOMPOK WANITA TANI (KWT) “MAWAR LANGGENG SARI” DESA PENGLIPURAN - I Gst B. Ngr. P. Putra; Anak Agung Ketut Jayawarsa; Ida Ayu Dinda Priyanka Maharani (LPPM Institut Desain dan Bisnis Bali, 2023)
Geographical conditions and natural conditions with cool climates are supporting factors for the ease of cultivating various types of plants in Penglipuran Village. The abundant supply of plants is utilized by the surrounding community to produce various kinds of food products. Utilization of this plant is able to produce a variety of processed products that are able to provide economic value. The processed products with natural potential include VCO (Virgin Coconut Oil) oil, jams with various flavors (pineapple, pumpkin and rosella), to various dry spices (ginger and turmeric). To increase interest from consumers, the resulting product has been properly packaged. This product is produced and marketed under the Kelompok Wanita Tani